Player Migration and Soccer Performance - Lago-Peñas, Carlos; Lago-Peñas, Santiago; Lago, Ignacio (Frontiers in Psychology, 2019)
The aim of this study is to examine the relationship between migrating soccer players and the annual ranking of the national teams according to the World Football Elo Rating. The sample includes annual data for 243 countries over the period 1994-2018. Migration is captured with the number of migrating players by country in the ‘big-five’ leagues. The causal relationship between the two variables is examined by using Granger causality test. Four control variables are included: the political regime, per capita income, population and regional soccer confederations. The results shed light on two crucial issues. First, causality mainly goes from national soccer performance to migrating soccer players rather than the other way around. Second, the timing of the two effects is quite different. While those players giving an outstanding performance when their national team is doing well are immediately bought by clubs from more highly ranked leagues (the shop-window effect), it takes at least four years for the additional skills acquired by migrated players to have a positive effect on the national soccer performance (the blending effect).